An intellectual property management framework for the College of Engineering of Ateneo de Naga University - Aguilar, Ryan S. (University of the Philippines Diliman, 2014)
This study aims at designing an intellectual property management framework for the College of Engineering of Ateneo de Naga University. The scientific-economic framework or the market-oriented approach was used as the "lens" in gathering good practices of intellectual property management. Good practices were gathered first from related literature. Two universities, specifically, the UP System and Bicol University, with existing intellectual property management underwent content analysis found on their web sites, annual accomplishment reports, official correspondence, etc to gather processes, policies and procedures that comply to the scientific-economic framework. Further verification was done through key informant interviews and email correspondence. A sample of 32 respondents composed of administrator; faculty and students were surveyed to get their opinion, awareness and attitude towards issues and practices of the scientific-economic framework. The data gathered were then reconciled with the findings from the two universities and related literature. Results showed that the College of Engineering would best follow the path taken by Bicol University since it is just starting to establish its intellectual property management. However, the limited commercialization success and the more mature processes of the UP system are worthy of emulating to further enhance its own.